Frontispiece: Mapping the Complete Photocycle that Powers a Large Stokes Shift Red Fluorescent Protein. Issue 5 (19th January 2023) - Wang, Ziyu; Zhang, Ya; Chen, Cheng; Zhu, Ruixue; Jiang, Jiaming; Weng, Tsu‐Chien; Ji, Quanjiang; Huang, Yifan; Fang, Chong; Liu, Weimin
Abstract : Photochemistry . In their Research Article (e202212209 ), Quanjiang Ji, Yifan Huang, Chong Fang, Weimin Liu et al. present a toolset for the mapping of the complete photocycle that powers a large Stokes shift red fluorescent protein.